2014
DOI: 10.1002/pssa.201431570
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of electrical properties of individual GaN nanowire-based ferroelectric field effect transistor

Abstract: Ferroelectric field effect transistors (FeFETs) using individual GaN nanowire as the conducting channel and Pb(Zr 0.52 Ti 0.48 )O 3 (PZT) thin film as the gate dielectric were fabricated, and their electrical properties were investigated. The curves of the transfer characteristics for the individual GaN nanowire-based FeFET are of counterclockwise hysteresis loops, as the gate voltage was swept from negative to positive and then back. The memory window is about 5 V, and an on/off current ratio is up to 10 3 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, the spin transport through a spin transistor mainly limited by the quality of the ferromagnetic source/drain contacts. To achieve a good spin transistor, the ferromagnetic contacts should be of good quality to reduce the destruction of injected spins at the contacts . In our early work, we have shown that the created potential barrier and anti‐ferromagnetic coupling at the graphene/TM interface reduce the magnetoresistance behavior due to destruction of injected spins at the contacts .…”
Section: Introductionmentioning
confidence: 98%
“…However, the spin transport through a spin transistor mainly limited by the quality of the ferromagnetic source/drain contacts. To achieve a good spin transistor, the ferromagnetic contacts should be of good quality to reduce the destruction of injected spins at the contacts . In our early work, we have shown that the created potential barrier and anti‐ferromagnetic coupling at the graphene/TM interface reduce the magnetoresistance behavior due to destruction of injected spins at the contacts .…”
Section: Introductionmentioning
confidence: 98%
“…The large polarization of ferroelectrics enables various materials as the channel, including Si, [4][5][6] Ge, 7) GaAs, 8) La 1.99 Sr 0.01 CuO 4 , 9) SrRuO 3 , 10) indium tin oxide, 11,12) indium gallium zinc oxide, 13) ZnO, [14][15][16] VO 2 , 17) and GaN. 18) After Böscke et al 19) and J. Müller et al 20) demonstrated ferroelectricity in Si-doped HfO 2 and Zr 0.5 Hf 0.5 O 2 ultrathin films, ferroelectric HfO 2 and its application to FGTs with a HfO 2 -based ferroelectric gate and a bulk Si channel have been intensively studied because of the compatibility with Si-CMOS technology and its scalability to technology nodes below 45 nm. 2,3,21,22) For example, in 2013, nonvolatile memory operation of an FGT with a 10 nm-thick HfO 2 layer fabricated using 28 nm technology was reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the difficulty and complexity of the fabrication process, most previous studies on FGTs with an NW channel have used a horizontal configuration in which NWs were horizontally placed between the source and drain electrodes on a ferroelectric film, similar to the structures of thin-film transistors. 6,15,17,18,25) The horizontal NWFGTs demonstrated nonvolatile modulation of the channel conductance by the ferroelectric gate underneath the NW channel, indicating that FGNWTs have potential applications in nonvolatile memory. However, their lateral dimensions were quite large; for example, the channel length of our NWFGTs was 5 or 10 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et.al. [19], investigated on the electrical properties of individual GaN nanowire based ferroelectric FETs. Mussener et et.…”
Section: Introductionmentioning
confidence: 99%